Comparative analysis of two different methods of anaerobic capacity assessment in sedentary young men - Klašnja Aleksandar; Drapšin Miodrag; Lukač Damir; Drid Patrik; Obadov Slavko; Grujić Nikola (Vojnosanitetski Pregled)
Background/Aim. The Wingate anaerobic test is a valid and reliable method of measuring anaerobic capacity. The aim of this study was to determine whether other modified test can be used instead of the Wingate test. Methods. A group of 30 sedentary young men were first tested with a cycle ergometer (classic Wingate test), and then with a dynamometer during 30 s of 'all out' leg extension exercise (modified Wingate test; WAnTe) in order to test anaerobic capacity. Subsequent correlations between these tests were made. Results. Peak power, mean power on cycling ergometer in absolute and relative values were 463 ± 105 W, 316.7 ± 63.8 W, 5.68 ± 1.17 W/kg, 3.68 ± 0.78 W/kg, respectively. On a dynamometer absolute and relative values of maximal and mean load in kg and power in Watts were 136.54 ± 21.3 kg, 1.67 ± 0.26; 128.65 ± 19.93 kg, 1.57 ± 0.24 kg, 657 ± 125.87 W, and 8 ± 1.54 W/kg, respectively. There was no correlation between 5 s intervals of the classic Wingate test and WAnTe during the first, fourth and fifth intervals, but in the second (r = 0.49, p < 0.05), third (r = 0.38, p < 0.05) and last 5 s intervals (r = 0.39, p < 0.05), and also in peak power and mean power (r = 0.42, p < 0.05 and r = 0.45, p < 0.05 respectively), a significant positive correlation was detected. Conclusion. A modified Wingate test of leg extension on a dynamometer in sedentary young men shows a correlation with the classic Wingate test only in parameters of peak power, and mean power and the second, the third and the last 5 s intervals. Because of that it should only be used for orientation, whereas for precise measurements of anaerobic capacity the classic Wingate test should be used.